Cyclin D2 – a potential biomarker in uterine corpus endometrial carcinoma through methylation chip and bioinformatic analysis - Wang, Lizhen; Qu, Wu; Yang, Zhifu (Frontiers in Oncology, 2025)
BackgroundThe incidence and mortality of uterine corpus endometrial carcinoma (UCEC) is increasing. Despite advances in diagnosis and treatment, the fundamental molecular mechanisms remain unclear to some extent. In this study, the role and clinical significance of Cyclin D2 (CCND2) in UCEC is discussed and explored.MethodsThe Infinium Methylation EPIC v2.0 BeadChip (935K chip) was utilized to analyze genomic DNA samples from four UCEC patients and four matched controls. Differentially methylated positions (DMPs) were identified, leading to the selection of the CCND2 gene as a candidate gene. Immunohistochemistry (IHC) was employed to validate the effects of CCND2 on UCEC. An analysis was conducted using the UALCAN and GSCA databases to compare the expression and methylation levels of the CCND2 gene promoter region between UCEC and adjacent normal tissues, as well as to explore the relationship between CCND2 expression and the methylation level of its gene promoter region. Subsequently, Cox regression and ROC analysis were performed with R software.ResultsThrough 935K chip detection, a total of 87,182 DMPs were identified in the whole genome of two groups. CCND2 was selected for further functional analysis. IHC results revealed that the positive expression of CCND2 in UCEC was significantly lower than in normal endometrial tissue (P < 0.05). TCGA datasets were analyzed to explore differential patterns involving mRNA and DNA methylation features associated with CCND2. The findings demonstrated a significant increase in the methylation level of CCND2 (P < 0.001), and a significant reduction in its mRNA expression (P < 0.001). Furthermore, the methylation level of the CCND2 gene promoter region exhibited a negative correlation with its mRNA expression (Cor. = -0.18, FDR = 0.018). Results from ROC analysis and survival analysis indicated that CCND2 expression was a prognostic indicator for UCEC (AUC = 0.956), with better survival in the high expression group (P = 0.0466).ConclusionThe study shows that UCEC has significantly abnormal DNA methylation patterns and expression profiles. Hypermethylation of the CCND2 promoter may reduce CCND2 expression and participate in tumor occurrence and development in UCEC. Hence, CCND2 shows promise as a potential biomarker for diagnosing and prognosticating UCEC.